Surface-enhanced Raman spectroscopic activity study on topological ZnSe nanostructures - Liu, Mei; Duan, Pengyi; Shafi, Muhammad; Liu, Wenying; Zhang, Wenjie; Zhang, Can; Hu, Xiaoxuan; Gao, Jing; Zhang, Chao (Frontiers in Physics, 2022)
Topological nanomaterials generally exhibit different defect structures, high specific surface areas, and varying band gaps. These special geometries, energy level structures, and interfacial interaction properties provide possibilities to explore interesting properties in the surface-enhanced Raman scattering (SERS). Such properties offer unexplored possibilities for exploring interesting physics and materials science in the field of surface-enhanced Raman Scattering (SERS) physical properties research and further enhancing substrate materials’ SERS activity. In this invited paper, the ZnSe topological nanowires crystallite structure was grown using the chemical vapor deposition method, twin defects were introduced, and a topological branched structure caused the corresponding changes in SERS activity were systematically investigated. On topological ZnSe nanowires, rhodamine 6G (R6G), methylene blue (MB), and crystalline violet (CV) molecules were detected by Raman spectroscopy. The Raman signal enhancement of MB on topological branched nanowires was about 1.9 times that of the trunk nanowires. Finally, the national standard measurement of malachite green (MG) content in water bodies and the direct spectral detection of 4-aminothiophenol (4-ATP) can be realized. The results suggest that semiconductor ZnSe topographical nanowires are an emerging class of SERS substrates, and a thorough investigation of the relationship between material structure and SERS performance in specific topological regions will provide new evidence for the principle of chemical enhancement of SERS, as well as recommendations for developing precisely functionalized SERS substrate nanomaterials.